Renal Reperfusion Lesion in Patients with Postrenal Obstruction - Yu. S. Sidorenko; N. D. Ushakova; A. A. Maslov; A. V. Yashkina (Общая реаниматология, 2007)
Objective: to define a role of renal reperfusion lesion in the development of renal failure in cancer patients after elimination of longstanding urinary tract occlusion.Subjects and methods. The study covered 26 patients in whom cancer disease was complicated by the development of urinary tract obstruction with evolving renal failure. All the patients received surgical treatment aimed at eliminating urinary tract occlusion. In the early postoperative period, progression of renal dysfunction was seen in all cases. The time course of changes in microcirculation, gas exchange, oxidative-antioxidative balance, and renal function were investigated to study the mechanisms responsible for the development of renal failure after surgery. Clinical and laboratory indices were analyzed before and 1 and 2 days after surgery.Results. The study has revealed that renal reperfusion lesion plays a prominent role in the development of renal failure in cancer patients after elimination of longstanding urinary tract obstruction, which should be borne in mind when preparing patients for surgery and managing them in the postoperative period, namely, to include membrane-stabilizers, antioxidants, and detoxicant therapy.